Interaksi Digital Tertanam Tidak Langsung: Bagaimana Pengalaman Digital di Luar Sekolah Mentransformasi Interaksi Sosial Siswa Sekolah Dasar Islam - Anisah; Amin Latif; Siswadi (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2026)
This study examines the transformation of social interaction among Madrasah Ibtidaiyah students in the context of digital educational leadership from the perspective of the sociology of education. Using a qualitative case-study design at MI Ma’arif NU 1 Dawuhan Wetan, data were collected through observation, interviews, and documentation involving 18 informants, and analyzed using the Miles and Huberman interactive model. The findings reveal a shift in students’ interaction patterns from active engagement to more passive forms, indicated by reduced verbal communication, declining social sensitivity, and selective peer relationships. Although digital devices are not used in school, students’ out-of-school digital experiences significantly shape their social behavior within the madrasah. The study shows that digital technology functions as a latent social structure internalized into interactional practices. It introduces the concept of indirect digitally embedded interaction and highlights the need to balance technology integration with meaningful social interaction in education.